THE EFFECT OF SUPPLY CHAIN MANAGEMENT AND COMPETITIVE ADVANTAGE ON COMPANY PERFORMANCE AT PT AHLINDO PERKASA ALAM - Lila Kaban; Jasmine Salim (Universitas Putera Batam, 2021)
Supply chain management, especially in manufacturing companies, is very important as the companies rely on the raw materials needed for production. Moreover, the success of a company is also determined by how it could gain competitive advantage to compete in the industry. It is proven that a company with effective supply chain management and competitive advantage would perform better. The purpose of this research is to see the effect of supply chain management and competitive advantage on company performance conducted at PT Ahlindo Perkasa Alam. This research uses quantitative method with Census sampling of 32 employees working in the company. The test results show that Supply Chain Management and Competitive Advantage have a positive significant effect on Company Performance at PT Ahlindo Perkasa Alam as much as 76.1%.